Friendship Is a Passport - Bryan, Julien Hequembourg (Tufts Archival Research Center, 2006)
Julien Bryan describes his early religious beliefs and the transformation, as a result of his experiences in WWI and filmaking, that led him to his belief in the common goodness of all people around the world.